Outsourcing library technical services operations practices in academic and special libraries in Metro Manila - Ramos, Marian S. (2004)
Outsourcing, which requires strategic decision and proactive professional decision-making, is a mainstream strategy of a business sector but its concept is not new to librarians. Outsourcing is the term given to the practice of contracting and internal activities or processes that would otherwise be performed by in-house employees to an external company or a group of individuals.